2017
DOI: 10.5535/arm.2017.41.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Improved Gait Speed After Robot-Assisted Gait Training in Patients With Motor Incomplete Spinal Cord Injury: A Preliminary Study

Abstract: ObjectiveTo evaluate the clinical features that could serve as predictive factors for improvement in gait speed after robotic treatment.MethodsA total of 29 patients with motor incomplete spinal cord injury received 4-week robot-assisted gait training (RAGT) on the Lokomat (Hocoma AG, Volketswil, Switzerland) for 30 minutes, once a day, 5 times a week, for a total of 20 sessions. All subjects were evaluated for general characteristics, the 10-Meter Walk Test (10MWT), the Lower Extremity Motor Score (LEMS), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Moreover, overground gait training using a wearable robot was demonstrated as more effective for dynamic balance than tethered-type robots [ 21 , 22 ]. They emphasized that facilitation of the trunk muscles for appropriate alignment of the body axis during weight-shifting movement could improve both static and dynamic balance control, followed by gait function [ 23 , 24 ]. Considering that gross motor function reflects dynamic balance [ 25 , 26 ], the simultaneous improvement of gross motor function and gait ability through RAGT was shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overground gait training using a wearable robot was demonstrated as more effective for dynamic balance than tethered-type robots [ 21 , 22 ]. They emphasized that facilitation of the trunk muscles for appropriate alignment of the body axis during weight-shifting movement could improve both static and dynamic balance control, followed by gait function [ 23 , 24 ]. Considering that gross motor function reflects dynamic balance [ 25 , 26 ], the simultaneous improvement of gross motor function and gait ability through RAGT was shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hwang et al [18] concluded that 30-min RAGT sessions for five times a week for a total of 20 sessions was useful in terms of ambulation. The improvement was higher among younger patients and those with shorter injury duration who had subacute incomplete motor SCI.…”
Section: Discussionmentioning
confidence: 99%
“…It uses sensory stimulation fed by proprioceptive feedback games, improving the neuroplasticity for functional recovery. Several studies have demonstrated the efficacy of Lokomat in improving the motor control of the body [4], the muscle mass regaining [5], the gait speed, and the muscle capabilities [6]. Furthermore, Lokomat provides objective assessments by using quantitative indicators offering the clinicians a complete perspective of the patient's physiological progress [7].…”
Section: Introductionmentioning
confidence: 99%